Proceedings of the work study school conference. Cranfield, March 1954 - College of Aeronautics, (Cranfield) (College of Aeronautics, 1954)
The Conference was arranged by request of the students of the Work Study School who attended the three courses. Out of a potential 56 students, 34 attended the Conference, and apologies for their absence were received from most of the remainder. The intention of the Conference was to give students the opportunity of renewing contact with their former colleagues, and to hear reports from people who had been putting Work Study into practice during the previous months, It was generally agreed that the Conference was a success, and arrangements are in hand for such conferences to be held annually.